The patient’s corporality in the therapeutic change process: A reflection on the importance of analyzing non-verbal communication of generic change indicators - Aquino Oliveira Lima, Isabela (2025)
The present essay aims to create a space for reflection on how the process of therapeutic change is currently conceived in Clinical Psychology. Specifically, it delves into the proposal of Generic Change Indicators and how the analysis of these indicators could be enriched by incorporating the analysis of non-verbal communication present in moments of therapeutic change. From this perspective, the essay seeks to answer the question: Could including the analysis of non-verbal communication in the observation of generic change indicators contribute to a broader understanding of the moments of change in which they occur? To address this, a theoretical journey is undertaken through the conceptions of therapeutic change present in the works of Eugene Gendlin and Paul Watzlawick, emphasizing the importance of developing an embodied and physical conception of therapeutic change. Subsequently, some empirical research on the topic is reviewed, leading to the conclusion that it is individuals as embodied beings who construct the therapeutic process. Therefore, the analysis of non-verbal bodily communication is fundamental for understanding Generic Change Indicators.